1998
DOI: 10.1111/j.1399-6576.1998.tb05101.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline and dextran after coronary artery surgery mobilises fluid excess and improves cardiorespiratory functions

Abstract: The present study documents that infused hypertonic saline with dextran just after the end of cardiac surgery resulted in mobilisation of the intraoperative fluid excess with increased urine output in the early postoperative period and improved gas exchange. Despite reduced need for extra i.v. fluid and decreased cumulative fluid balance, after HSD infusion the patients had increased filling pressures of the heart with improved cardiac output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 17 publications
1
28
0
6
Order By: Relevance
“…Auch in den Bereichen der 37,41,45] und Gefäß-chirurgie [12,38] sowie bei Intensivpatienten mit "systemic inflammatory response syndrome" (SIRS)/Sepsis [19] oder erhöh-tem intrakraniellen Druck [20, 22] konnten vorteilhafte Effekte eines hypertonen Volumenersatzes -allerdings bei deutlich verlängerten Infusionszeiten von 15-30 min -verzeichnet werden. Ähnlich wie im traumatisch-hypovolä-mischen Schock spielt das Ischämie/Reperfusionsereignis in der Kardiochiurgie (Aortencrossclamping) eine herausragende Rolle in der Entstehung einer systemisch inflammatorischen Antwort.…”
Section: Hämodynamische Reaktionen Nach Präoperativer Hypervolämi-schunclassified
See 1 more Smart Citation
“…Auch in den Bereichen der 37,41,45] und Gefäß-chirurgie [12,38] sowie bei Intensivpatienten mit "systemic inflammatory response syndrome" (SIRS)/Sepsis [19] oder erhöh-tem intrakraniellen Druck [20, 22] konnten vorteilhafte Effekte eines hypertonen Volumenersatzes -allerdings bei deutlich verlängerten Infusionszeiten von 15-30 min -verzeichnet werden. Ähnlich wie im traumatisch-hypovolä-mischen Schock spielt das Ischämie/Reperfusionsereignis in der Kardiochiurgie (Aortencrossclamping) eine herausragende Rolle in der Entstehung einer systemisch inflammatorischen Antwort.…”
Section: Hämodynamische Reaktionen Nach Präoperativer Hypervolämi-schunclassified
“…Auch in den Bereichen der Kardio- [7,37,41,45] und Gefäß-chirurgie [12,38] sowie bei Intensivpatienten mit "systemic inflammatory response syndrome" (SIRS)/Sepsis [19] oder erhöh-tem intrakraniellen Druck [20,22] konnten vorteilhafte Effekte eines hypertonen Volumenersatzes -allerdings bei deutlich verlängerten Infusionszeiten von 15-30 min -verzeichnet werden.…”
Section: Hämodynamische Reaktionen Nach Präoperativer Hypervolämi-schunclassified
“…2 Studies have shown that hypertonic solutions whether combined with colloids such as dextran or 6% hydroxyethyl starch or not promote a negative water balance, improved cardiac output, decreased systemic vascular resistance and reduce the need for blood products. [3][4][5][6][7][8][9] These benefits have also been shown for volume replacement with hypertonic solutions during the postoperative period following off-pump coronary artery bypass grafting. 10 Off-pump coronary artery bypass grafting reduces blood losses, myocardial infarction, acute renal failure, mediastinitis, stroke and prolonged orotracheal intubation particularly in subgroups of higher-risk patients.…”
Section: ' Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21] Furthermore, the positive fluid balance, incurred due to fluid administration, is also reduced. This is the result of improved renal function with an accompanying increase in urine output.…”
mentioning
confidence: 99%